2007
DOI: 10.1007/s00005-007-0047-1
|View full text |Cite
|
Sign up to set email alerts
|

Total antioxidant status and 8-hydroxy-2′-deoxyguanosine levels in gingival and peripheral blood of periodontitis patients

Abstract: Introduction: The aim of this study was to determine 8-OHdG concentration as a biomarker of oxidant-induced DNA damage and to assess total antioxidant status (TAS) in gingival and peripheral blood during periodontal lesion. Materials and Methods: The study included 56 untreated periodontitis patients (26 with aggressive periodontitis, and 30 with chronic periodontitis (CP). The control group consisted of 25 healthy volunteers without pathological changes in the periodontium. Competitive ELISA was used to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
4
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 32 publications
11
92
4
2
Order By: Relevance
“…Various studies have associated periodontitis with compromised antioxidant activities. Studies [26,27] have reported lower TAOC in saliva, gingival blood and peripheral blood of subjects with chronic periodontitis as compared to healthy control group as observed in our study. Al Bayaty et al [28] has observed lowered antioxidant in smokers as compared to non-smokers.…”
Section: Discussionsupporting
confidence: 70%
“…Various studies have associated periodontitis with compromised antioxidant activities. Studies [26,27] have reported lower TAOC in saliva, gingival blood and peripheral blood of subjects with chronic periodontitis as compared to healthy control group as observed in our study. Al Bayaty et al [28] has observed lowered antioxidant in smokers as compared to non-smokers.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, information regarding the changes in circulating antioxidant level is required to investigate the relationship between periodontitis and blood oxidative stress. Some previous studies have demonstrated that the levels of blood antioxidant status in subjects with periodontitis were lower than those in subjects with healthy gingiva [31,33], while others have suggested that there were no significant differences in serum or plasma antioxidant concentration between the group with chronic periodontitis and controls [11,34]. Several methodologies are now available to evaluate the antioxidant status in blood samples, and the relationship between blood anti-oxidative status and periodontal condition may differ depending on which kinds of antioxidant molecules were examined.…”
Section: Relationship Between Periodontitis and Blood Oxidative Stresmentioning
confidence: 87%
“…However, the above studies were cross-sectional, and it is not clear whether the increase of blood oxidative stress is the cause or result of periodontitis. In addition, some studies showed no significant differences in serum lipid peroxidation [10] and oxidative DNA damage in venous blood [31] between the subjects with and without periodontitis. It has, therefore, not yet been elucidated if serum lipid peroxidation in periodontal involvement causes oxidative DNA damage.…”
Section: Relationship Between Periodontitis and Blood Oxidative Stresmentioning
confidence: 97%
“…8-Hydroxydeoxyguanosine was found to be higher in samples from subjects with chronic periodontitis compared with periodontally healthy controls in saliva, but no data on serum levels were reported [ 83 , 85 ]. Another study by Konopka et al [ 42 ] analyzed oxidative stress markers by puncture and blood collection from a gingival papilla and found increased 8-OHdG in aggressive and chronic periodontitis. This measure of DNA oxidative damage in GCF was consistently higher also in studies from Japanese populations [ 43 , 83 , 84 ].…”
Section: Dna Damage Caused By Oxidative Stressmentioning
confidence: 98%